Faut-il se souvenir du républicanisme anglais ? L’héritage intellectuel du républicanisme anglais dans le temps long - Myriam-Isabelle Ducrocq (XVII-XVIII)
From a purely superficial institutional perspective–the Interregnum spanned eleven years (1649-60), and the republican regime proper, the Commonwealth, only lasted three (1649-53) – it may seem that English republicanism was but a brief parenthesis which could be easily forgotten. However, if one considers its intellectual origins, the abundance of theoretical debate at the time of the First English Revolution, the importance of its reception across the British Isles, Europe and America and the manifest or subterranean role it played in transatlantic revolutions and its legacies, it appears as a legitimate object of study for historians of political thought; which is why there has been sustained interest in the history of this intellectual tradition over the past few decades.